TOLERANCE AND ACCEPTABILITY OF INTRAVENOUS KETAMINE THERAPY FOR TREATMENT RESISTANT DEPRESSION: A MIXED METHODS ASSESSMENT - Mansoor, Sawera; Khan, Khalid Hayat; Faridi, Manzoor Ahmed (Journal of Pakistan Psychiatric Society, 2023)
Objectives: This study was conducted to evaluate the response of treatment resistant depression to IV ketamine therapy protocol and explore the perspectives of patients regarding the acceptability of this treatment modality.Study Design: Mixed methods assessment including Quasi experimental design and Qualitative interviews.Place and Duration of Study: The study was conducted at Department of Psychiatry, Fauji Foundation Hospital, Rawalpindi from Jan to Jun 2022.Subjects and Methods: Through purposive sampling, 14 patients of treatment resistant depression were made part of the sample. Hamilton Rating scale for Depression (HAM-D) was used to measure response to 6 Ketamine infusions administered over 2 weeks. Paired t-test was applied to analyze changes in HAM-D scores compared to pretreatment baseline at 1 hour, 2 weeks and 1 month after last dose of ketamine using SPSS 26.0. Semi structured interviews were conducted to explore the attitudes of patients regarding ketamine treatment. Thematic analysis was carried out and data driven themes were identified.Results: There was a statistically significant improvement in severity of depression scores at 1 hour and 2 weeks after the last dose of ketamine. This effect was not significantly sustained at 1 month after the last dose. Some patients expressed initial hesitation related to safety of this treatment, citing comparisons with General anesthesia. By the end of treatment, most patients were keen to be advocates for the access to Ketamine therapy due to experiencing rapid transformational effects on severe depressive symptoms.Conclusion: IV Ketamine therapy was found to be a rapid, effective and acceptable tool for treatment resistant depression; however its longer-term effects could not be established.